2023
DOI: 10.1051/e3sconf/202346201035
|View full text |Cite
|
Sign up to set email alerts
|

Farm waste collection organizing based on information system

Irina Krasnikova,
Irina Kulibaba

Abstract: The article defines the relevance of the problem of utilisation of waste generated in the course of farms' activities, regardless of their size and type of activity. The possibility of using software tools to organise the processes of collection, storage, sorting, and transportation for the subsequent disposal of such waste is established. The use of methods of structural analysis, synthesis, statistical analysis, information modelling allowed to establish all key objects and processes with their characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…Such specialized software tools perform their work on the basis of digital models reflecting the behavior of real objects [5,11]. At the same time, to control processes, develop managerial decisions or refine the model, the data obtained not only from sensors or stations located in fixed places, but also data from people who use software tools in their activities when interacting with natural objects [12][13][14] are used.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such specialized software tools perform their work on the basis of digital models reflecting the behavior of real objects [5,11]. At the same time, to control processes, develop managerial decisions or refine the model, the data obtained not only from sensors or stations located in fixed places, but also data from people who use software tools in their activities when interacting with natural objects [12][13][14] are used.…”
Section: Resultsmentioning
confidence: 99%
“…If the obtained results of the design phase of the conducted study are compared with the results of related studies, the similarity of the use of methodologies and the nature of the obtained process implementation models may be established. The engineering of simulation models is required when developing concepts for the implementation and use of specialized software tools that control complex processes in ecosystems of companies, changes in the states of which depend on a variety of parameters (including random) [5,12,13,15]. With their help, it is possible to form professional competencies with minimal use of consumables and other resources, while reducing the injury hazard when performing certain types of complex work [9].…”
Section: Discussionmentioning
confidence: 99%
“…The use of such software, on the one hand, allows ensuring practice-oriented nature of the educational process, and on the other hand, does not allow creating and comprehensively managing the learning curve of students. At the moment, many technologies and tools have been developed that allow simulating natural objects and processes of any complexity [9,10,[13][14][15]. At the same time, such resources can become the basis for the tools used to perform practice-oriented tasks and to check the mastery of didactic units at each stage of the educational process.…”
Section: Resultsmentioning
confidence: 99%
“…The tools and their corresponding modeling algorithms were used in the work performed, as the obtained result in its structure corresponds to the results of other studies using our stated research methods. When creating specialized software products before the development stage, works on the analysis and formalization of objects and processes of the problem domain were carried out [2,5,11]. Such an approach was carried out in the current study, which resulted in data suitable for use at the stage of program code creation.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of literature sources related to the digital transformation of agricultural processes, development of software products or its components has shown that the fundamental stage that determines the features of programming functionalities, implementation of development and its further use is the design stage [5][6][7]. At the design stage it is required to establish all the key objects that will participate in the development process, the rules of their interaction and the features of external influences [4,7].…”
Section: Methodsmentioning
confidence: 99%